Criminalization of Perpetrators of Spreading Radicalism Ideology Leading to Terrorism - Caleb Rainold Blesstian Marcellino; Wiwik Afifah (International Journal of Social Sciences and Humanities, 2025)
The development of radicalism in the modern era makes it easy for someone to be influenced and join a radical organization. For example, for someone who does not have in-depth knowledge about religion. This makes it easier for the perpetrators of terrorism to spread their teachings to others so that they gain new knowledge and eventually become involved in acts of terrorism. The research aims to find out the regulation of punishment against perpetrators of the spread of radical terrorism. This research uses a normative legal research method using a statutory approach and a conceptual approach. The results of the study show that the Eradication of Terrorism Crimes is currently appropriate and well implemented, as evidenced by the decreasing number of acts of terrorism that occur. However, it needs to be further clarified, especially Radicalism Terrorism which has not been expressly regulated in laws and regulations. Regulations regarding the Criminalization of Perpetrators of Spreading Radicalism of Terrorism are contained in Article 12B Paragraph (3) and Article 13A of the Terrorism Law and Article 45A Paragraph (2) of the Electronic Law which explains that anyone who spreads violent teachings to commit acts of terrorism can be charged and punished.